Scaphoid Fracture Patterns—Part One: Three-Dimensional Computed Tomography Analysis - Drijkoningen, Tessa; Mohamadi, Amin; Luria, Shai; Buijze, Geert A. (Journal of Wrist Surgery, 2019)
Objective Using three-dimensional (3D) computed tomography models of acute scaphoid fractures, we looked for differences between volumetric size of the fracture fragments, recognizable groups, or a shared common fracture area.Methods We studied 51 patients with an adequate computed tomography scan of an acute scaphoid fracture using 3D modeling. Fracture surfaces were identified and fragment volumetric size of the fracture fragments was measured. A principal component analysis was used to find groups. Density mapping was used to image probable common fracture areas in the scaphoid.Results Forty-nine of 51 fractures had a similar pattern. It was not possible to identify subgroups based on fracture pattern. The mean volumetric size of the fracture fragments of the proximal (1.45 cm3 ± 0.49 cm3 standard deviation [SD]) and distal fracture fragments (1.53 cm3 ± 0.48 cm3 SD) was similar. There was a single common fracture area in the middle third of the bone. In the distal third, there were no horizontal fractures through—but only directly proximal to—the tubercle suggesting that these would be best classified as distal waist fractures.Conclusion Acute scaphoid fractures mainly occur in the middle third of the bone and tend to divide the scaphoid in half by volumetric size of the fracture fragments. There were two distinct grouping patterns: fractures through the proximal and middle third were horizontal oblique, whereas fractures of the distal third were vertical oblique. It seems that scaphoid fractures might be classified into proximal pole fractures, a range of waist fractures, and tubercle avulsion fractures.Level of evidence This is a Level IV study.
Keywords: scaphoid fracture; classification